Pacifiplex: an ancestry-informative SNP panel centred on Australia and the Pacific region. (January 2016) - Santos, Carla; Phillips, Christopher; Fondevila, Manuel; Daniel, Runa; van Oorschot, Roland A.H.; Burchard, Esteban G.; Schanfield, Moses S.; Souto, Luis; Uacyisrael, Jolame; Via, Marc; Carracedo, Ángel; Lareu, Maria V.
Graphical abstract: Highlights: Pacifiplex is a 29 AIM-SNP assay amplified in one SNaPshot ® reaction. 125 pg minimum DNA input and high amplification success of low template samples. Differentiates four major population groups: Africa, Europe, East Asia and Oceania. The HGDP-CEPH panel is a suitable reference set for this region. CEPH Oceanians provide an appropriate proxy for Aboriginal Australian diversity. Abstract: The analysis of human population variation is an area of considerable interest in the forensic, medical genetics and anthropological fields. Several forensic single nucleotide polymorphism (SNP) assays provide ancestry-informative genotypes in sensitive tests designed to work with limited DNA samples, including a 34-SNP multiplex differentiating African, European and East Asian ancestries. Although assays capable of differentiating Oceanian ancestry at a global scale have become available, this study describes markers compiled specifically for differentiation of Oceanian populations. A sensitive multiplex assay, termed Pacifiplex, was developed and optimized in a small-scale test applicable to forensic analyses. The Pacifiplex assay comprises 29 ancestry-informative marker SNPs (AIM-SNPs) selected to complement the 34-plex test, that in a combined set distinguish Africans, Europeans, East Asians and Oceanians. Nine Pacific region study populations were genotyped with both SNP assays, then compared to four reference population groups from the HGDP-CEPH human diversity panel. STRUCTURE analyses estimated population cluster membership proportions that aligned with the patterns of variation suggested for each study population's currently inferred demographic histories. Aboriginal Taiwanese and Philippine samples indicated high East Asian ancestry components, Papua New Guinean and Aboriginal Australians samples were predominantly Oceanian, while other populations displayed cluster patterns explained by the distribution of divergence amongst Melanesians, Polynesians and Micronesians. Genotype data from Pacifiplex and 34-plex tests is particularly well suited to analysis of Australian Aboriginal populations and when combined with Y and mitochondrial DNA variation will provide a powerful set of markers for ancestry inference applied to modern Australian demographic profiles. On a broader geographic scale, Pacifiplex adds highly informative data for inferring the ancestry of individuals from Oceanian populations. The sensitivity of Pacifiplex enabled successful genotyping of population samples from 50-year-old serum samples obtained from several Oceanian regions that would otherwise be unlikely to produce useful population data. This indicates tests primarily developed for forensic ancestry analysis also provide an important contribution to studies of populations where useful samples are in limited supply.